Eksplorasi Budaya Melalui Kereta Api Sebagai Pengalaman Wisata di Negeri Sakura : Culturan Exploration Through Railways as A Tourism Experience in The Land of Rising Sun - Susan Agustina Putri; Revania Keisha Az Zahra; Wanda Reza; Dianni Risda (Undiksha Press, 2025)
Trains in Japan not only function as a mode of transportation that can help people in making it easier to get to their respective destinations, but also as a means to promote culture and tourism. So that it raises its own uniqueness which is then recognized by the public and attached to the country of Japan because of its unique culture. This research aims to provide an overview of how Japanese trains play a role in introducing Japanese cultural values to foreign tourists and strengthening these values in local communities. Using the literature study method in several journals, this research will identify the cultural elements introduced through train symbolism, station facilities, and services during the journey. In addition, this research will also be useful for those who want to understand or explore more about Japanese culture, especially in public transportation modes.